The Future of Latin American Library Collections and Research Contributing and Adapting to New Trends in Research Libraries - Acosta-Rodríguez, Fernando (Seminar on the Acquisition of Latin American Library Materials, 2012)
Selected papers from the annual conference of the Seminar on the Acquisition of Latin American Library Materials